Wear Inducing Phase Transformation of Plasma Transfer Arc Coated Tools during Friction Stir Welding with Al Alloy - Kuan-Jen Chen; Fei-Yi Hung; Truan-Sheng Lui; Yong-Ren Shih (Journal of Engineering)
The friction stir welding process (friction stir welding/processing, FSW/FSP) has wear problems related to stirring tools. In this study, the plasma transfer arc (PTA) method was used with stellite 1 powders (Co-based) to coat on the head of a SKD61 stirring tool (SKD61-ST1) in order to investigate the wear performance and phase transformation of SKD61-ST1 after FSW. Under the same experimental parameters, the wear data were compared with the high-speed steel SKH51 (tempering material SKH51-T and annealed material SKH51-A) and tungsten-carbide cobalt (TCC). Results showed the PTA coating was a γ-Co solidification matrix with M7C3 and M23C6 carbides. After FSW, the wear resistance of SKD61-ST1 was better than that of SKH51-A and SKH51-T and lower than that of TCC. The SKD61-ST1, SKH51-A, and SKH51-T stirring tools exhibited sliding wear after FSP, where the pin and shoulder of the stirring tool formed a phase transfer layer on the surface, and the peeling of the phase transfer layer caused wear weight loss. The main phase of the phase transfer layer of the SKD61-ST1 tool was Al9Co2. The affinity and adhesion energy of the Co-Al phase was lower than that of Fe-Al phase, and the phase transfer layer of the SKD61-ST1 tool was thinner and had lower coverage, thereby increasing the wear resistance of the SKD61-ST1 stirring tools during FSW.